Scarlet and Black Slavery and Dispossession in Rutgers History - White, Deborah Gray; Fuentes, Marisa (Rutgers University Press, 2016)
The work of the Committee on Enslaved and Disenfranchised Population in Rutgers History. Visit the project's website at http://scarletandblack.rutgers.edu
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: History / African American & Black; History; Electronic books